Antiviral responses versus virus-induced cellular shutoff: a game of thrones between influenza A virus NS1 and SARS-CoV-2 Nsp1 - Khalil, Ahmed Magdy; Nogales, Aitor; Martínez-Sobrido, Luis; Mostafa, Ahmed (Frontiers in Cellular and Infection Microbiology, 2024)
Following virus recognition of host cell receptors and viral particle/genome internalization, viruses replicate in the host via hijacking essential host cell machinery components to evade the provoked antiviral innate immunity against the invading pathogen. Respiratory viral infections are usually acute with the ability to activate pattern recognition receptors (PRRs) in/on host cells, resulting in the production and release of interferons (IFNs), proinflammatory cytokines, chemokines, and IFN-stimulated genes (ISGs) to reduce virus fitness and mitigate infection. Nevertheless, the game between viruses and the host is a complicated and dynamic process, in which they restrict each other via specific factors to maintain their own advantages and win this game. The primary role of the non-structural protein 1 (NS1 and Nsp1) of influenza A viruses (IAV) and the pandemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), respectively, is to control antiviral host-induced innate immune responses. This review provides a comprehensive overview of the genesis, spatial structure, viral and cellular interactors, and the mechanisms underlying the unique biological functions of IAV NS1 and SARS-CoV-2 Nsp1 in infected host cells. We also highlight the role of both non-structural proteins in modulating viral replication and pathogenicity. Eventually, and because of their important role during viral infection, we also describe their promising potential as targets for antiviral therapy and the development of live attenuated vaccines (LAV). Conclusively, both IAV NS1 and SARS-CoV-2 Nsp1 play an important role in virus-host interactions, viral replication, and pathogenesis, and pave the way to develop novel prophylactic and/or therapeutic interventions for the treatment of these important human respiratory viral pathogens.